The impact of change management on organizational excellence Analytical study of a number of government banks in Thi-Qar Governorate - Assistant Lecturer. Rana Abdul Sattar Al-Hammadi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research is concerned with knowing the extent of the impact of change management on organizational excellence and reviewing the literature that searches for the relationship between the two variables and which emphasized the importance and role of change management in defining and mapping features of organizational excellence in organizations. To achieve the goal of the current research, a model was built and selected that explains and explains the relationship and impact of the two variables (change management and organizational excellence). In order to test the research hypotheses, a sample of the heads of people was chosen in a number of government banks in Thi -Qar Governorate (Al-Rashid Bank - Al-Rafidain Bank - the Iraqi Commercial Bank) where a questionnaire was prepared for this purpose, as the researcher distributed (50) a questionnaire that was retrieved from it ( 40) A questionnaire, which was approved for statistical analysis , The data were analyzed using a number of statistical methods through the use of a program (SPSS) to reach the required results, which came to confirm the research hypotheses, which is the existence of a correlation between change management and organizational excellence, as well as the effect of change management on organizational excellence in the performance of the work of the organizations under research.